2020
DOI: 10.1051/0004-6361/202038559
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of chromospheric heating by acoustic waves

Abstract: Aims. Our aim is to investigate the role of acoustic and magneto-acoustic waves in heating the solar chromosphere. Observations in strong chromospheric lines are analyzed by comparing the deposited acoustic-energy flux with the total integrated radiative losses. Methods. Quiet-Sun and weak-plage regions were observed in the Ca II 854.2 nm and Hα lines with the Fast Imaging Solar Spectrograph (FISS) at the 1.6-m Goode Solar Telescope on 2019 October 3 and in the Hα and Hβ lines with the echelle spectrograph att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 54 publications
5
32
2
Order By: Relevance
“…Integrating velocity power over frequency range 2-50 mHz we find that magneto-acoustic waves carry just sufficient energy to heat the chromosphere in solar plage regions. This is in contrast to the claims by Fossum & Carlsson (2005a) and recent observations by Abbasvand et al (2020).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Integrating velocity power over frequency range 2-50 mHz we find that magneto-acoustic waves carry just sufficient energy to heat the chromosphere in solar plage regions. This is in contrast to the claims by Fossum & Carlsson (2005a) and recent observations by Abbasvand et al (2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the energy flux available at a height of 800 km (i.e., ∼10 4 W m −2 ) is just sufficient to balance the estimated radiative losses in the layers above this height, as estimated by Withbroe & Noyes (1977). This is in contrast to previous studies where acoustic flux was found to be insufficient to compensate for the radiative losses (Fossum & Carlsson 2005b;Beck et al 2009;Abbasvand et al 2020Abbasvand et al , 2021. Additionally, the acoustic wave flux in the height range of 250-600 km is much larger than estimated in previous studies pertaining to quiet Sun regions (Wunnenberg et al 2002;Straus et al 2008;Bello González et al 2009).…”
Section: Resultsmentioning
confidence: 72%
“…This way, significant portions of the radiative losses could be compensated via acoustic wave flux which has been previously converted to magnetoacoustic wave flux in the regions with the inclined fields. Abbasvand et al(2020b) concluded that the flux contained in magneto-acoustic waves with frequencies up to 20 mHz is sufficient to balance the radiative losses of the quiet chromosphere up to 1000-1400 km height. The difference with the previous results can be attributed to the existence of magnetic shadows (areas with reduced wave power at a given frequency), which prevents part of the acoustic energy reaching chromospheric heights in the network and plage regions, similar to observations by Kontogiannis et al (2014Kontogiannis et al ( , 2016.…”
Section: Wave Heating Of the Large-scale Chromospherementioning
confidence: 99%
“…Magnetic reconnection and heating due to waves are not independent mechanisms however, since magnetic reconnection can be a source of waves (Verwichte et al 2004;Jess et al 2008;Luna et al 2008;Li & Zhang 2012;Provornikova et al 2018), and waves can produce instabilities needed to trigger reconnection processes (Isobe & Tripathi 2006;Lee et al 2014;McLaughlin et al 2009). Moreover, recent advances in observational instrumentation and simulation capabilities imply that wave-based heating could be a viable process for maintaining the high temperatures of the solar atmosphere (Abbasvand et al 2020;Yadav et al 2021a;Abbasvand et al 2021). These new results have drawn renewed interest in wave heating mechanisms, both observationally and theoretically.…”
Section: Introductionmentioning
confidence: 99%